The global minimum tax on environmental accountability efforts within the extractive sector of Zimbabwe - Basimanyane, Dorcas K. (University of Pretoria, 2025)
Mini Dissertation (LLM (Trade and Investment Law in Africa)--University of Pretoria, 2025.